2012
DOI: 10.1111/iju.12023
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index influences prostate cancer risk at biopsy in Japanese men

Abstract: Abbreviations & AcronymsObjectives: To determine the relationship between body mass index and prostate cancer risk at biopsy in Japanese men, and to compared the risk with that of Caucasian men. Methods: We retrospectively evaluated 3966 men with prostate-specific antigen levels from 2.5 to 19.9 ng/mL who underwent an initial extended prostate biopsy. Using logistic regression, odds ratios of each body mass index category for risk of prostate cancer and high-grade disease (Gleason score Ն4 + 3) were estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
18
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 34 publications
(64 reference statements)
5
18
1
1
Order By: Relevance
“…Several prospective and retrospective studies have suggested that obese men were more likely to harbor clinically significant prostate cancer and were at higher risk of prostate cancer mortality and recurrence after primary treatment [4][5][6]8,17,[21][22][23][24]. Both overweight and obese men in our cohort were observed to be at significantly increased risk of having clinically significant prostate cancer detected on biopsy, thereby further supporting the growing body of evidence that links obesity to cancer aggressiveness.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Several prospective and retrospective studies have suggested that obese men were more likely to harbor clinically significant prostate cancer and were at higher risk of prostate cancer mortality and recurrence after primary treatment [4][5][6]8,17,[21][22][23][24]. Both overweight and obese men in our cohort were observed to be at significantly increased risk of having clinically significant prostate cancer detected on biopsy, thereby further supporting the growing body of evidence that links obesity to cancer aggressiveness.…”
Section: Discussionsupporting
confidence: 80%
“…In our series, only 6.8% were obese based on the WHO definitions. This value is higher than rates reported in both Korean (1.4%) and Japanese (1.7%) prostate cancer detection study cohorts [17,18]. Comparatively, obesity was markedly more prevalent in other Western studies.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…1 Body mass index (BMI) might influence the risk of developing other urological cancers, especially renal cell carcinomas (RCC).…”
mentioning
confidence: 99%